Combating Dysmenorrhea: the Effectiveness of Exercise and Effleurage Massage Among Adolescent Girls - Amrina Nur Rohmah; Eka Sri Wijayanti (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
Dysmenorrhea is a condition characterized by menstrual pain, commonly presenting as lower abdominal cramps that may radiate to the back. The primary cause is often linked to hormonal imbalances. Non-pharmacological approaches, such as physical exercise and massage therapy, have been shown to help alleviate the symptoms. This study aimed to evaluate the effectiveness of exercise for dysmenorrhea and effleurage massage in reducing menstrual pain among adolescent girls at the Melak Health Vocational School. A quasi-experimental design with a two-group pre-test and post-test approach was used. The study population included all female students from classes X, XI, and XII, with a total of 48 participants selected through total sampling. Pain intensity was measured using the Numeric Rating Scale (NRS), and the data were analyzed using the Wilcoxon and Mann-Whitney tests. The results indicated that both interventions significantly reduced menstrual pain, with a p-value of 0.000 (p < 0.05) for each group. Furthermore, the Mann-Whitney test revealed a significant difference between the two interventions, with a p-value of 0.001 (p < 0.05). Exercise for dysmenorrhea demonstrated a greater average effect than effleurage massage, with a mean difference of 11.25. Based on these findings, it is recommended that adolescent girls consider both exercise and effleurage massage as non-pharmacological options for managing menstrual pain, with exercise for dysmenorrhea proving to be the more effective therapy.